The Use of Digital Learning Media in Islamic Religious Education in Elementary Schools: A Literature Study - Danira Keysha Maharani; Amelia; Egin Pratiwi; Muhammad Afandi (Ilmina: Journal of Education and Counseling, 2026)
This study aims to examine the use of digital learning media in Islamic Religious Education (IRE) classes in elementary schools through a literature review approach. The method used is a literature review with a qualitative approach. Data sources were obtained from 10 national journal articles published between 2022 and 2025 that were relevant to the research topic. Data collection was conducted through documentation, namely reading, identifying, recording, and grouping important information from each article. The data were analyzed using qualitative descriptive methods through the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that various digital learning media used in PAI instruction in elementary schools include digital comics, Wordwall, animated videos, YouTube, Google Classroom, educational websites, interactive applications, and Artificial Intelligence (AI)-based media. The use of these media has been proven to enhance learning motivation, interest in learning, attention focus, student engagement, and the learning outcomes of students. The effectiveness of digital media is influenced by an engaging media design, alignment with student characteristics, the availability of technological infrastructure, and the teacher’s role as a learning facilitator. Thus, digital learning media can serve as an effective alternative in creating PAI instruction that is more engaging, interactive, innovative, and meaningful, in line with the demands of technological advancements in the digital age.